Images of the west in the Moroccan contemporary novel - El Kaidi, Youssef (Université mohamed ben abdellah, Faculté des lettres et des sciences humaines Dhar El Mahraz, Fès, 2017)
This dissertation takes the Moroccan contemporary novel as its subject matter. The main purpose behind this study is to investigate the way Moroccan contemporary novelists represent the West/Other in their novels and how that representation affects their conception of the Self. Due to the geographical proximity and the historical, cultural and political interaction between Morocco and Europe, the theme of cultural otherness has always been, and is still, a vital component of the novel genre in Morocco. Deploying the eclectic approach with more emphasis on the postcolonial approach, the question of cross-cultural representation and the construction of alterity is, therefore, explored in various ways. The study demonstrates that the image of the West is variable and takes different manifestations; it is not homogeneous and static but heterogeneous and mutable depending on the historical, socio-cultural and political conditions determining the relationship between the Self and the Other as well as on the psychological and ideological backgrounds of individual writers. With many Moroccan contemporary novelists, the West is seen as a utopian world to be emulated and a hub for human development at all levels while with many others it is denigrated and undervalued and its technical and scientific achievements are belittled. Sometimes both contradictory images of the West are dialectically negotiated, which reflects Moroccan novelists’ ambivalence towards the West. Some postcolonial Moroccan novelists tend to deconstruct and scathingly criticize the system of cultural values in both the West and the East. In this case, a third cultural and socio-political utopian reality is sought, usually because neither the West nor the East live up to the expectations of justice, equality and human dignity. This study is divided into three parts. The first part establishes the general theoretical framework through the introduction and clarification of a set of concepts such as representation, identity and Occidentalism. The second part is an introduction to the Moroccan novel, its developmental stages, contexts and concerns. The third part is practical and analytical followed by a conclusion that summarizes the overall results of the study and the prospects it opens up.
Keywords: West; Moroccan; Novel; Image.